Understanding Middle School Teachers’ Levels of Efficacy to Meet the Needs of Young Adolescents - Erika Daniels (Middle Grades Review, 2022)
Middle school students are in even more need of social and emotional support due to the cognitive, social, and emotional changes occurring at this stage of their development (Caskey & Anfara, 2014), and their teachers are key players in providing what is needed. Unfortunately, there are few Institutions of Higher Education that offer programs or coursework focused on young adolescents’ unique and specific needs (Howell, et al., 2016). This contrast with calls for school contexts that are intentionally designed to support young adolescents (Bishop & Harrison, 2021) and raises questions about whether and how middle school teachers are prepared to meet the wide-ranging needs of their students. Therefore, the purpose of this study was to understand how middle school teachers feel about their skills and knowledge in terms of supporting students’ cognitive, social, and emotional needs. The teachers’ perspectives shed light on ways educator preparation programs might refine and enhance their curriculum and instruction to better meet teachers’ needs in terms of supporting middle school students most effectively. Five themes arose from data analysis, which were 1) Appreciation of young adolescents, 2) Knowledge of young adolescent development, 3) Confidence and growth, 4) Strategies for working with young adolescents behaviorally and academically, and 5) External stressors. The findings offer insights for teachers, teacher education programs, and school districts to create supportive and productive educational contexts for all learners.
Keywords: teacher efficacy; middle school; young adolescents